Wireless and wired strain gage studies - Yong, Soon Lai (2018)
Using wireless strain gauge systems to collect data is a more effective and safer method compared to using wired strain gauge systems when monitoring the conditions of a structure. This is because the wireless strain gauge system does not require manual monitoring on-site. To test the accuracy and feasibility of the wireless system compared to wired system, the wireless strain gauge system was applied to monitor strain generated on the rail fastening clips by the train passing over the rail at around 70 km/hr. As the rail clips are the system that secure the rail track’s alignment and ensures that there is constant contact between the rail and sleeper. By identifying the critical areas on the clips, the strain gauge was mounted to determine the strain and stress conditions that leads to the failure of the clips. With a combination of laboratory testing and modelling, the strain experienced by the clips were predetermined before an on-site experiment was carried out. The strain data of the clips during installation and the cyclical stress and strain that acted on the clip were compared with the laboratory-determined one to determine the accuracy of the wireless strain gauge. The results showed that the installation process would burden the clips with a strain that is very close to the yield condition of the material. The cyclical strain experienced by the clips varies with the peak or non-peak periods of the train services. At the highest strain reading in the peak period recorded, the maximum principal stress exceeds the yield stress of the material.